The pedagogical practice since adidactic situations in mathematics - Jiménez-Espinosa, Alfonso; Sánchez-Bareño, Daysy Maite (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this article is to characterize the pedagogical practice from the use of non-didactic situations in Mathematics classes. This research uses a qualitative approach, under the technique of action research, with the use of instruments such as: non-participant observation, open-ended questionnaire, researcher's field diary, focus groups and design and application of specific non didactic situations. The population studied was made up of 4 teachers and their students who belong to basic education. When the teacher faces the vision of his class and the same class being observed by others, mediated by the collective reflection on his practice; he begins to have another attitude and another way of seeing the dynamics of a class. Likewise, the implementation of non-didactic situations improves the dynamics of the math class. Motivation and enthusiasm are some of the emotions expressed by students towards learning, revealing the importance of innovating, generating challenges and imbalances, so that the teaching of Mathematics is more than just repeating the contents and mechanizing them.